Ion target impact energy during Type I edge localized modes in JET ITER-like Wall. (9th July 2015) - Guillemaut, C; Jardin, A; Horacek, J; Autricque, A; Arnoux, G; Boom, J; Brezinsek, S; Coenen, J W; De La Luna, E; Devaux, S; Eich, T; Giroud, C; et al.
Abstract: The ITER baseline scenario, with 500 MW of DT fusion power and Q = 10, will rely on a Type I ELMy H-mode, with Δ W = 0.7 MJ mitigated edge localized modes (ELMs). Tungsten (W) is the material now decided for the divertor plasma-facing components from the start of plasma operations. W atoms sputtered from divertor targets during ELMs are expected to be the dominant source under the partially detached divertor conditions required for safe ITER operation. W impurity concentration in the plasma core can dramatically degrade its performance and lead to potentially damaging disruptions. Understanding the physics of plasma-wall interaction during ELMs is important and a primary input for this is the energy of incoming ions during an ELM event. In this paper, coupled Infrared thermography and Langmuir Probe (LP) measurements in JET-ITER-Like-Wall unseeded H-mode experiments with ITER relevant ELM energy drop have been used to estimate the impact energy of deuterium ions (D + ) on the divertor target. This analysis gives an ion energy of several keV during ELMs, which makes D + responsible for most of the W sputtering in unseeded H-mode discharges. These LP measurements were possible because of the low electron temperature ( T e ) during ELMs which allowed saturation of the ion current. Although at first sight surprising, the observation of low T e at the divertor target during ELMs is consistent with the 'Free-Streaming' kinetic model which predicts a near-complete transfer of parallel energy from electrons to ions in order to maintain quasi-neutrality of the ELM filaments while they are transported to the divertor targets.